Treatment Response to Sofosbuvir and Ribavirin in Chronic Hepatitis C Patients and Comparison of Naive and Treatment Experienced Patients - Muhammad Ikhlaq, Maryam Jalil, Syed Dawar, Muhammad Ashraf, Muhammad Ikhlaq, Maryam Jalil, Syed Dawar, Muhammad Ashraf (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Sofosbuvir is on the world organization’s list of essential medicines, the most effective and safe medicines needed in health system. It plays a special role in treatment of chronic hepatitis C and offers many advantages due to its high potency, low side effects, oral administration, and high barrier to resistance. Objectives: To compare the treatment response in treatment naive and treatment experienced chronic hepatitis C patients treated with sofosbuvir and ribavirin to determine the efficacy of this drug combination. Methods: In this experimental study 104 chronic hepatitis C patients with positive polymerase chain reaction (PCR) for hepatitis C virus (HCV) and high alanine aminotransferase (ALT) levels were included. Out of them 66 (63.5%) were treatment naive (received treatment for the first time) and 38 (36.5%) were treatment experienced. Sofosbuvir 400mg once a day in combination with ribavirin was given for 6 months and treatment responses were noted at 4, 12 and 24 weeks. SPSS version 21 was used to analyze the data. Results: The end treatment response in 104 chronic hepatitis C patients was calculated in which 99 (95.2%) patients responded to the therapy. 63 (95.5%) treatment naive patients and 36 (94.7%) treatment experienced responded to the therapy. End treatment response (ETR) in chronic hepatitis C patients to sofosbuvir and ribavirin was irrespective to their gender and genotypes and test of significance came out as insignificant (p > 0.05). Conclusion: Sofosbuvir is effective for both treatment naive and treatment experienced chronic hepatitis C patients. This regimen is equally effective for both genders and all genotypes of hepatitis C.